The global diversity and distribution of lizard clutch sizes. Issue 9 (11th June 2020) - Meiri, Shai; Avila, Luciano; Bauer, Aaron M.; Chapple, David G.; Das, Indraneil; Doan, Tiffany M.; Doughty, Paul; Ellis, Ryan; Grismer, Lee; Kraus, Fred; Morando, Mariana; Oliver, Paul; et al.
Abstract: Aim: Clutch size is a key life‐history trait. In lizards, it ranges over two orders of magnitude. The global drivers of spatial and phylogenetic variation in clutch have been extensively studied in birds, but such tests in other organisms are lacking. To test the generality of latitudinal gradients in clutch size, and their putative drivers, we present the first global‐scale analysis of clutch sizes across lizard taxa. Location: Global. Time period: Recent. Major taxa studied: Lizards (Reptilia, Squamata, Sauria). Methods: We analysed clutch‐size data for over 3, 900 lizard species, using phylogenetic generalized least‐square regression to study the relationships between clutch sizes and environmental (temperature, precipitation, seasonality, primary productivity, insularity) and ecological factors (body mass, insularity, activity times, and microhabitat use). Results: Larger clutches are laid at higher latitudes and in more productive and seasonal environments. Insular taxa lay smaller clutches on average. Temperature and precipitation per se are unrelated to clutch sizes. In Africa, patterns differ from those on other continents. Lineages laying small fixed clutches are restricted to low latitudes. Main conclusions: We suggest that the constraint imposed by a short activity season, coupled with abundant resources, is the main driver of large‐clutch evolution at high latitudes and in highly seasonal regions. We hypothesize that such conditions – which are unsuitable for species constrained to laying multiple small clutches – may limit the distribution of fixed‐clutch taxa.